1976
DOI: 10.1126/science.941019
|View full text |Cite
|
Sign up to set email alerts
|

Screwworm Eradication: Inadvertent Selection for Noncompetitive Ecotypes During Mass Rearing

Abstract: The rapid fixation of a rare allelic form of alpha-glycerol phosphate dehydrogenase is related to a loss of competitive ability in nature of factory-reared screwworm flies. The increase in frequency results from selection for survival under conditions of domestication and rapid development at high constant temperatures in the factory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 22 publications
(12 reference statements)
2
41
0
2
Order By: Relevance
“…Temperature selection may be responsible since Gpd alleles have appeared sensitive to climatic temperature in other insects such as screwworm flies 46 and Colias butterflies. 47 Jacobina is located inland at an elevation of approximately 500 m, in contrast to the coastal or Amazonian sites near sea level, and probably has differing annual temperature cycles; unfortunately, maps of isotherms were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature selection may be responsible since Gpd alleles have appeared sensitive to climatic temperature in other insects such as screwworm flies 46 and Colias butterflies. 47 Jacobina is located inland at an elevation of approximately 500 m, in contrast to the coastal or Amazonian sites near sea level, and probably has differing annual temperature cycles; unfortunately, maps of isotherms were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Mate-selection processes may be changed because unmated or previously mated females will have restricted means of escape (Bartlett 1984b) 6. Dispersal characteristics, specifically adult flight behavior and larval dispersal, may be severely restricted by laboratory conditions (Bush et al 1976) Furthermore, if a genetic differentiation has developed between laboratory and field populations, this may lead to genetic isolation (Oliver 1972). Also, positive correlation has been found between the incompatibility of such races and the differences between the environments (laboratory, field) where races occur, and for the length of time two populations have been isolated.…”
Section: Genetic Changes In Laboratory Coloniesmentioning
confidence: 91%
“…They predicted that complete mating failure could not occur because the sexual activities of mass-reared flies still occurred at the lower light-intensity levels that were required to stimulate mating activity in wild flies; however, when the mating time of a mass-reared strain is later than that of a wild strain, as in the present case, the probability of copulation among wild flies could increase. Bush et al (1976) demonstrated that the sexual activity time of massreared screwworms, Cochliomyia hominivorax (Coquerel), was later than that of wild screwworms. They concluded that this difference was one of the causes of increased infestation during eradication programs in the southwestern United States, because the mating of wild flies was completed among themselves before mass-reared flies 312 T. MATSUYAMA and H. KUBA became competent for sexual activity.…”
Section: Discussionmentioning
confidence: 99%